The combination of Ile225Thr polymorphism of Fcg receptor IIB gene and hypersensitiveness as risk factor for human systemic lupus erythematosus in chinese populations - Pan Faming; Ye Dongqing; Zhang Kechun; Li Xiangpei; Xu Jianhua; Chen Hong; Su Hong (Wolters Kluwer Medknow Publications, 2007)
Background: The aim of this study was to investigate the role of FcgRIIB gene in susceptibility to systemic lupus erythematosus (SLE) using family-based association study and to examine possible interaction between the Ile225Thr (rs1050501, exon 5) polymorphism of Fcg receptor IIB gene and hypersensitivity. Objectives: A total of 119 patients with SLE from 95 nuclear families, aged 14 to 78 years, according to the American College of Rheumatology (ACR) 1997 criteria were recruited. In addition, 316 family members of these patients were also genotyped. Seventy patients and their 70 normal siblings from 95 nuclear families were selected by the case-combined-control design. Materials and Methods: A family-based association study was used to explore the relationship between gene polymorphism and SLE. We studied a single-nucleotide polymorphisms (SNPs) encoding non-synonymous substitution in the FcgRIIB gene with respect to genetic susceptibility to SLE, the FcgRIIB gene were genotyped by restriction fragment length polymorphism (RFLP) method. The interaction of gene-environment was assessed by conditional logistic regression model. Results: Among 119 SLE patients, The frequencies of FcgRIIB Ile225Ile, Ile225Thr and Thr 225 Thr genotypes were 8.1%, 61.3% and 30.6%. Univariate (single-marker) family-based association tests (FBATs) demonstrated that variant allele at SNP rs1050501, in exon 5 of FcgRIIB gene was significantly associated with genetic susceptibility to SLE in additive model (exon 5, Z=3.707, P =0.00020). Transmission/disequilibrium test (TDT) and sibship disequilibuium test (SDT) analysis showed an excess of the allele of 225Thr ( Ile225Thr loci) from heterozygous parents to affected offspring (c 2=7.14, P =0.0105); Moreover, conditional logistic regression results showed that there was statistically significant multiplicative interaction of FcgRa!B gene and the Hypersensitiveness [c 2=5.013, P =0.024; OR=2.444, CI (1.126-5.309)]. Conclusions: Our findings provide strong evidence suggesting a Ile225Thr polymorphism might be the susceptibility factor of SLE; a possible gene-environment interaction between hypersensitiveness and Ile225Thr mutation in Chinese population.